Comparison of subchondral lesion size between clinical and non-clinical medial trochlear ridge talar osteochondritis dissecans in dogs - Gielen, I.; Van Ryssen, B.; Coopman, F.; van Bree, H. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
In this retrospective study of nine dogs exhibiting bilateral medial trochlear ridge talar osteochondritis dissecans (MTRT-OCD) and unilateral hind limb lameness, we compared subchondral lesion size in limbs with visible lameness, with contralateral lesions that were not associated with any visible lameness. All MTRT-OCD lesions were imaged by radiography and computed tomography (CT). The dimensions of subchondral bone lesions were measured (length, width and depth) using CT software. Similar to a method used in humans, the estimated volume (length x width x depth) and cross sectional area (length x width) were calculated and compared. We found that MTRT-OCD lesions causing visible lameness were significantly larger, and were associated with more joint thickening and degenerative joint disease than contralateral lesions that were not associated with any apparent lameness. As in the disease of shoulder osteochondritis dissecans, there is probably a correlation between the size of MTRT-OCD lesions and the symptoms of lameness.
Keywords: Dogs; computed tomography; osteochondritis dissecans; talus